Analyzing the effect of composition, density, and the morphology of the "free" carbon phase on elastic moduli in silicon oxycarbide ceramics. Issue 4 (April 2023) - Haseen, Shariq; Kroll, Peter
Abstract: We perform atomistic simulations to model structures and calculate elastic properties of silicon oxycarbide ceramics. We explore individual parameters – composition, density, carbon content – to disentangle mutual dependencies that are difficult to separate in experimental studies. Each parameter is studied through dynamic simulations at finite temperatures for a wide range of temperatures. With multi-million atom models in simulation boxes as large as 40 nm, we reveal a hitherto "hidden" parameter: the morphology of the "free" carbon phase. Embedding, distribution, and interconnection of the carbon phase inside the amorphous matrix of SiCO severely impact the material's mechanical properties. As a consequence, we call for the development of new characterization techniques that will quantify the morphology of carbon in this and similar systems.